2019
DOI: 10.3390/ijerph16162985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Safety Warning on Domperidone Prescribing for Geriatric Patients in South Korea: Analysis of National Insurance Claim Data

Abstract: Domperidone is a dopamine antagonist used for the symptomatic management of nausea and vomiting. Many countries banned or add a black box warning due to an increased risk of serious adverse cardiac effects. In 2014, the Korea Ministry of Food and Drug Safety also released a safety warning to carefully consider adverse cardiac effects when prescribing domperidone. Therefore, we conducted this study to analyze the impact of the safety warning on domperidone prescribing. This study included patients 65 years or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Many researchers have used ITSA methodologies to evaluate the effectiveness of healthcare policies. 8,[14][15][16][17][18][19] In recent years, several studies have suggested a scientific process and recommendations for ITSA including methodology and reporting. We performed an ITSA comparing the utilization pattern of metoclopramide before and after the publication of the safety letter with reference to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have used ITSA methodologies to evaluate the effectiveness of healthcare policies. 8,[14][15][16][17][18][19] In recent years, several studies have suggested a scientific process and recommendations for ITSA including methodology and reporting. We performed an ITSA comparing the utilization pattern of metoclopramide before and after the publication of the safety letter with reference to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The safety letter included recommendations with regard to the indications, prescription, and dosage of metoclopramide However, the effects of a safety letter from the MFDS during post-marketing surveillance are mixed. Previous studies have shown that a safety letter from the MFDS can change the drug utilization pattern, 8 whereas other studies have reported that safety letter from the MFDS had a limited impact on treatment use in clinical practice. 9 A safety letter from the MFDS is an important national policy option in Korea for pharmacovigilance and risk management.…”
Section: Introductionmentioning
confidence: 99%
“…corpo médico para as práticas de prescrição mais segura. Um estudo realizado porCarvalho et al, (2022) descreve a visão dos preceptores de residência médica, e afirma sobre a importância da atualização cientifica de forma contínua para atuarem com qualidade em suas preceptorias e assistência.O sexo feminino se destacou com 78% se corroborando com os resultados do estudo realizado porRhew, Han & Oh (2019) que demonstrou maior utilização do domperidona por mulheres idosas do serviço de seguro de saúde nacional nos anos de 2011 e 2016 na Coreia do Sul, representando respectivamente 66% e 63%. É importante citar que as mulheres apresentam maior risco no prolongamento do intervalo QT e desenvolver TdP como demonstram alguns estudos que o sexo feminino devido as mudanças hormonais que ocorrem com o envelhecimento podem contribuir com a indução/inibição da CYP3A influenciando assim no metabolismo dos fármacos(Cotreau et al, 2005), além de que pode apresentar fisiologicamente intervalo de QT em torno de 20 milisegundos (ms) a mais do que o sexo masculino(Prado et al, 2017).…”
unclassified